2015
DOI: 10.1039/c5fd00149h
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule spectroscopy and imaging over the decades

Abstract: As of 2015, it has been 26 years since the first optical detection and spectroscopy of single molecules in condensed matter. This area of science has expanded far beyond the early low temperature studies in crystals to include single molecules in cells, polymers, and in solution. The early steps relied upon high-resolution spectroscopy of inhomogeneously broadened optical absorption profiles of molecular impurities in solids at low temperatures. Spectral fine structure arising directly from the position-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 202 publications
1
73
0
1
Order By: Relevance
“…Following the development of single-molecule detection techniques (1824), the first demonstration of FRET at the single-molecule level was published in 1996 (25). It suggested that single-molecule FRET (smFRET) could be used to study dynamic processes and identify transient conformations and interactions between macromolecules labeled with a donor-acceptor dye pair.…”
mentioning
confidence: 99%
“…Following the development of single-molecule detection techniques (1824), the first demonstration of FRET at the single-molecule level was published in 1996 (25). It suggested that single-molecule FRET (smFRET) could be used to study dynamic processes and identify transient conformations and interactions between macromolecules labeled with a donor-acceptor dye pair.…”
mentioning
confidence: 99%
“…Single-molecule biophysics was until the last decade mainly used to investigate properties of molecules in vitro; in particular, to dissect the asynchronous intramolecular state transitions of molecules that cannot be seen in the enable average. These techniques have allowed us to study the mechanics of molecular machines at exceptional precision, and the development has been reviewed for example in (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Спектроскопия одиночных молекул (СОМ) является мощным оптическим методом изучения внутренней динамики диэлектрических твердотельных сред, который позволяет полностью устранить ансамблевое (и соответственно пространственное) усреднение получаемых данных о веществе и получить ценную информацию об изучаемых процессах на микроуровне (см., например, [10,11]). Индивидуальные спектры возбуждения люминесценции одиночных флуоресцентных молекул (ОМ), внедренных в прозрачную твердотельную матрицу в качестве спектрального нанозонда, содержат уникальные данные о динамике и других параметрах матрицы в ближайшем локальном окружении таких молекул.…”
Section: Introductionunclassified